SISTEM MONITORING KESEHATAN BERBASIS INTERNET OF THINGS (IoT) - Silvia Ratna (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
The internet is now an important part of our lives and has enabled many of the machines and devices that we use in our daily lives to be remotely monitored and controlled through Internet of Things (IoT) technology. smart health applications have become a very fast growing sector. For someone with heart disease, the value of the Heart Rate (HR), Heart Rate Variability (HRV) and Body Temperature (ST) are considered as vital parts that must be measured regularly. In this study, an Android-based application will be developed that can monitor the value of HR, HRV and ST for patients who must always be under the supervision of a doctor. The measurement system, which consists of sensors that can be used, continuously measures the condition of the patient's heart rate. Then send the measurement results on the android interface via an internet connection. Based on the results of research that has been done by proposing a The prototype Health Monitoring System produces excellent data accuracy. The measurement system created allows patients to move in their own social environment, and allows patients to live their daily lives comfortably.